Ο ANTONI RUBIÓ I LLUCH ΩΣ ΙΣΤΟΡΙΟΓΡΑΦΟΣ ΚΑΙ Η ΣΥΜΒΟΛΗ ΤΟΥ ΣΤΗ ΜΕΛΕΤΗ ΤΩΝ ΚΑΤΑΛΑΝΩΝ ΣΤΗΝ ΕΛΛΑΔΑ ΤΟΝ 14ο ΑΙΩΝΑ - ΝΤΟΥΡΟΥ-ΗΛΙΟΠΟΥΛΟΥ ΜΑΡΙΑ (Eoa kai Esperia, 2007)
Antoni Rubió i Lluch (1856-1937) was professor in the University ofBarcelona and founder of the Institute of Catalan Studies. He had devoted hislife collecting material about the Catalans in Greece in the 14th century andhe has published several books and articles. His fundamental work was the«Diplomatari del Orient català», based on research on the Archives ofBarcelona, Venice, Vatican and Palermo, which sheds light on the Catalanperiod of Athens and its relations with the Kingdom of Aragon. His work isvery useful for scholars or anyone who wants to enrich his knowledge in thisarea. Furthermore he has translated Greek literature and his correspondencewith the authors is an important source of knowledge on that period.